Design and Analysis of A Stair Climbing Hand Trolley using Design of Experiment (DOE) - Mohd Noh, Mahadhir Aiman; Nawawi, Azli (Progress in Engineering Application and Technology, 2023)
In the absence of a lift and escalator, it is difficult for users to transport heavy loads from the ground level to the higher floors of a building. Human effort is the best solution to transport heavy loads by using a stair climbing hand trolley. However, it will affect the users while handling heavy loads if using excessive efforts, which can result in musculoskeletal disorder (MSD). To minimize the risk of suffering musculoskeletal problems, it is necessary to build a system capable of lifting weights while navigating steps to reduce musculoskeletal disorder (MSD) occurred. Thus, this study can be the basis or benchmark for prospective researcher for knowledge on the state. To begin, this study focuses on design improvement using SolidWorks software and analysis of a stair climbing hand trolley using Design of Experiment (DOE). For the design improvements, the basket trolley and basket mounting were added using SolidWorks software to increase the efficiency of a stair climbing hand trolley. SolidWorks Simulation was used to analyze the design of this study and the results obtained from the Finite Element Analysis (FEA) which are yield strength and displacement. The purpose of this study aims to identify the significant parameters and optimum setting for the stair climbing hand trolley. This study is expected to achieve several outputs such as yield strength, and displacement from the three parameters, which are material, ply angle and ply thickness. As a result, alloy steel was chosen since the material has the highest yield strength where the failure will happen much longer than stainless steel and aluminium alloy. Thus, Design of Experiment by using optimum parameters (material, ply thickness and ply angle) has proven to increase the efficiency of a stair climbing hand trolley by improving its material and mechanical properties.